INVESTIGATION OF NEW SCHEMES OF ROTOR-PISTON ENGINES BY THE METHOD OF SPLITTING OF THERMODYNAMIC PROCESSES - Дихановський B. M. (Proceedings of National Aviation University (archive), 2021)
Theoretical bases of the developed method of splitting of thermodynamic processes for research of new schemes of rotor-piston engines are stated. A complex thermodynamic process is considered as a sequence of several simple thermodynamic processes. Using the developed method, a comparative analysis of a six-stroke rotary-piston engine with a traditional four-stroke carburetor piston engine was performed.